Growing great contact center communicators - Drake-Knight, Nick (Henry Stewart Talks, 2009)
The model of excellence, Explicit standards, Contact center coaching, Personal drivers, Continue and begin, Observation or judgment?, Structure of well-done-ness, Language that hinders, Language that helps, Can't to can